Territorial Sovereignty And The Role Of Wilāyat Al-Ḥukmī In Establishing The Beginning Of Kamariah Months In Indonesia - Novi Arisafitri; Rizal Ramadhan; Youla Afifah Azkarrula (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The divergence in determining the beginning of Kamariah (Hijri) months consistently triggers controversy, primarily due to differences in methodology, schools of thought, and the concept of mathla’ (horizon). Although Indonesia adopts a mathla’ concept based on its national territory, in practice, there remains a significant distortion regarding the precise geographical boundaries of the Indonesian territory in relation to the Kamariah calendar calculations.As stated in Law of the Republic of Indonesia No. 43 of 2008 concerning State Territory, the jurisdiction of the Unitary State of the Republic of Indonesia (NKRI) includes land, sea, and air space. This raises critical questions: What are the juridical boundaries of Mathla’ Wilāyah al-Ḥukmī in Indonesia for the determination of the beginning of the Kamariah months? Furthermore, how is Mathla’ Wilāyah al-Ḥukmī applied within the framework of the MABIMS Neo-Hilal Visibility Criteria?